(untitled) (The Review of Diabetic Studies, 2025)
This paper explores the emerging humanitarian and ethical crisis stemming from the forced transfer of domestic workers to psychiatric hospitals under false claims of mental illness. Recruitment agencies and employers have reportedly abused emergency medical systems by contacting ambulance services to forcibly remove workers under the guise of psychiatric instability. Such incidents not only violate basic human rights and medical ethics but also disrupt emergency medical operations and divert critical resources from genuine emergencies. The study analyzes the sociopsychological and legal implications of these forced transfers and their impact on ambulance service efficiency. Using a mixed-method approach that combines field interviews with emergency personnel and secondary data on ambulance utilization, this research highlights the systemic weaknesses that enable exploitation through emergency response systems. The article concludes with strategic recommendations for policy enforcement, ethical training, and improved verification mechanisms to safeguard both domestic workers’ rights and emergency response efficiency.